Comparison of consumers and industry managers concerning food packaging elements. Issue 3 (11th November 2020) - Konstantoglou, Aggeliki; Folinas, Dimitris; Fotiadis, Thomas
Abstract : Purpose: The importance of packaging in the food industry lies in its multifunctional nature. Packaging elements can come from studying the contribution of different research disciplines and functional areas: marketing, logistics, food technologies and the environment. The purpose of this study aims to identify and evaluate packaging elements in the food industry from a holistic point of view. Design/methodology/approach: Primary data are collected through two research initiatives via questionnaires, which were filled by 1, 219 consumers of food products and 390 managers (executives) working in the packaged food products market, which is a very important and competitive sector in Greece. Findings: In general, the findings reveal that all the key players in the food supply chain understand and appreciate the multifunctional and multidisciplinary nature of packaging. Moreover, informational, operational, physical and visual elements are all of high importance. These findings lead to the conclusion that all executives from different operational areas of a business should be involved in packaging design, despite the fact that they may have different perspectives concerning the different elements involved in the packaging in the food supply chain. Research limitations/implications: The research confirms that: (1) health and nutrition are two interrelated concepts that receive constant attention from the food industry, as well as from governments and consumers and (2) the quality of a food product is inextricably linked to the quality of its packaging. Naturally, there were also significant differences between the various roles, while differences were also observed in the appreciation of the packaging elements between consumers and executives in the food industry. Practical implications: The study proves the need for narrowing the gap among managers' perceptions regarding packaging by adopting practices and approaches in an integrated manner. Social implications: From the analysis of the relevant literature, the authors of the present study note that there is a lack of research concerning the main elements of packaging in the food industry from a holistic point of view. This view will encompass the needs of marketing and logistics managers, food technologists and executives are responsible for environmental issues, as well as the consumers of food products. By identifying the significance that all the above perceive against the various elements of the packaging of retail products, manufacturers can take into consideration the elements that are highly appreciated by both cohorts. Originality/value: Although the multidisciplinary nature of the package is very clear, most studies in the literature focus on either its impact on consumer behavior and its use as a communication/differentiation tool or as a tool that has significant implications for the efficiency of the logistics systems throughout the supply chain, as well as for the particular features/properties and the environmental awareness. This study sought to fill the abovementioned gap, by recognizing its importance among marketing, logistics, food technology and corporate social responsibility managers, including issues concerning environmental awareness, and how consumers perceive the data on the packaging.